Waves in ducts described by means of potentials - Snakowska, Anna (Archives of Acoustics, 2007)
The waveguide theory constitutes an important part of classical wave theory and the resultsare applied in many practical devices. The aim of the paper is to present a coherent approachto the problem of propagation of sound and electromagnetic waves in ducts by means of potentials.The potential concept simplifies the field description and discussion of some basicconditions, posed on mathematical expressions, which come from their physical meaning.These conditions are, for example, the Euler equation for sound waves or the Lorentz gaugecondition for electromagnetic field. The analyze of the respected field is carried out by meansof velocity potential for sound waves and the Hertz potentials for electromagnetic waves. Theacousto-electromagnetic analogies are derived and discussed for infinite circular and rectangularduct. The cut-off frequencies, the waveguide impedance and the power transmitted alongthe duct is discussed in reference to these analogies.